Scheduling of inbound trucks at a cross-docking facility: Bi-objective vs bi-level modeling approaches - Golias, Mihalis; Saharidis, Georgios K.D.; Boile, Maria; Theofanis, Sotirios (My University, 2012)
This paper examines the problem of scheduling of inbound trucks to the inbound doors at a cross-docking facility. The authors optimize for two conflicting objectives: minimize the total service time for all the inbound trucks and minimize the delayed completion of service for a subset of the inbound trucks, which are considered as preferential customers. The problem is formulated as a bi-objective and as a bi-level mixed integer problem. Due to the nature of the former and the complexity of the latter formulation, a genetic algorithm and a k-th best based algorithm are proposed as the solution approaches. Computational examples are used to discuss the advantages and drawbacks of each formulation. Copyright © 2012, IGI Global.